(3efgL cej eY OQGSI MGdIs - (3eDjO(B, (3GdaVds ((3YeGf(B:s (3eDSSI GdhQGb ddfTQ hGdJhRjY(B,s, 2022)
(3eaghe GdJbjje, CSGdjH GdefgL Gdcej, JYQja GdeTQhY (BDefinition of Project (3, eaghe GdeTQhY aj EWGQ fehPL (BICOM (3NUGFU GdeTQhY HTcd YGe, Jbjje GdeTQhY, EOGQI GdeTQhY, OhQI MjGI GdeTQhYGJ, JbSje hJUfja GdeTQhYGJ, JNWjW GdeTQhY , JfXje GdeTQhY, GdbjGOI aj GdeTQhY, GdeaGVdI Hjf GdeTQhYGJ Ydi CSGS GdQjGVjGJ GdJWHjbjI, MSGH GdbjeI GdeSJbHdjI dQCS GdeGd aj GdeTQhY, JMdjd GdJYGOd aj Jbjje GdeTQhY, GdJcGdja GdJaGVdjI aj Jbjje GdeTQhY, WQjbI GdGfMOGQ aj MSGH Gdbje GdeSJbHdjI ddXGgQI, fehPL Gdfbd aj JMOjO ehGbY GdehGQO GddGReI dJfajP GdeTQhY, WQjbI GdSeHdcS aj ebGQfI HOGFd GdeTQhYGJ GdeJhaQI dGNJjGQ GdHOjd GdCeKd, CSdhH GdJNUjU aj hVY GdHQGeL hSjGSGJ GdYed Vef eQMdI GdJfajP GdaYdj ddeTQhY, eaghe GdbQGQ (BDecision (3hYedjI GJNGP GdbQGQ, GJNGP GdbQGQGJ aj MGdGJ GdHjFI GdeNJdaI, GJNGP GdbQGQGJ aj MGdI YOe GdJCcO, TLQI GdbQGQGJ aj GNJjGQ GdeTQhYGJ, bhGYO GdSjWQI aj TLQI GdbQGQGJ, eaghe THcGJ GdYed hCfhGYgG, JUeje THcGJ GdYed Ydi CSGS Cf GdCfTWI Ydi GdCSNe (B(AoA) (3, JUeje THcGJ GdYed Ydi CSGS GdYbO (B(AoN)(3, OhQ THcGJ GdYed aj GdGSJZdGd GdCeKd ddhbJ hGdehGQO GdeGOjI, GdeDKQGJ GdNGQLjI hGdOGNdjI aj JfajP GdeTQhY ,GdELQGAGJ GddGReI dEMGdI GdeTQhY ddJfajP, CSdhH LGfJ (BGANTT(3aj GdJNWjW hGdQbGHI Ydi JfajP GdeTQhYGJ, eaghe hNWhGJ JWHjb GSdhH GdeSGQ GdMQL, GdGMJjGWGJ GdRefjI, LOhdI JMdjd GdJcGdja MSH GdhbJ GdeHcQ (BET (3hGdhbJ GdeJCNQ, eHGOdI GdcdaI HGdhbJ GdHQeLI GdNWjI aj eHGOdI GdcdaI HGdhbJ, eaghe GdHQGeL, CSdhH Jbjje heQGLYI JfajP GdHQGeL (BPERT(3, GSJNOGe GdHQGeLjGJ GdLGgRI hGdMGShH, CSdhH (BPERT/ Time- Costs (3aj GdQbGHI Ydi JfajP GdeTGQjY, OQGSI MGdI TGedI, CgejI JhRjY GdehGQO Hjf GdCfTWI , bhGYO JhRjY GdehGQO GdHTQjI GdeJGMI hGSJZdGdgG HGdTcd GdCeKd(B.s
(3eQGLY U(B.535 (3edGMb U(B.543s
Keywords: (3EOGQI GdCYeGds; (3GdeTQhYGJ(B- (3JfXje hEOGQIs